Pengaruh Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Pegawai DPUPR Kabupaten Barito Utara - Noorhayati, Noorhayati (Jurnal Ekonomi STIEP ( JES ), 2019)
The aim of this research is to analyze the influence of motivation and job satisfaction through staffperformance of DPUPR North Barito Regency. Data about those variable was collected by conductinterviews with questionnaire. The sample is selected by using the technique simple random sampling, whichtotaled 30. The hyphoteses are tested using multiple regression analysis by SPSS for Windows 19.0. Theresult showed that : 1) the motivation and job satisfaction has a significant and simultan influence throughstaff performance DPUPR North Barito Regency; 2) the motivation hasn’t a significant impact through staffperformances on staffs of DPUPR North Barito Regency; the job satisfaction has a significant impactthrough staff performances of DPUPR North Barito Regency; and then 3) the most dominan variableaffecting through staff performance of DPUPR North Barito Regency is the job satisfaction.